Women's Speech In A State of Anger: A Neuropragmatic Study - Rahmadani Sabrian; Gusdi Sastra; Ike Revita (JURNAL ARBITRER, 2019)
This research aims to describe and to translate the emotional prosody patterns through Praat program and also to describe types of speech acts used by female characters in an emotional state in the film "Hati 7 Cinta 7 Wanita". Emotional prosody of speech is analyzed by using the Praat program, which is then classified into types of particular speech acts. The emotional prosody patterns can be seen in the melodic accent and the temporal accent. In the melodic accent, speech that uses declarative and interrogative mode makes the tone flow increased, and the speech that uses imperative mode makes the tone flow decreased. In the temporal accent, the speeches with the longest and the shortest anger emotions are the ones that use declarative mode. Next, the woman character is known to use four types of speech act when getting angry, which are; literal direct speech act, non-literal direct speech act, literal indirect speech act, non-literal indirect speech act.